2016
DOI: 10.1590/0104-07072016004660015
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Control Actions: Analysis Based on the Access and Primary Health Care Quality Improvement Program

Abstract: The study's aim was to analyze primary health care delivered to people with tuberculosis on a national level, based on the information collected by an external assessment implemented by the Programa de Melhoria do Acesso e da Qualidade da Atenção Básica. This cross-sectional study with a quantitative approach used data from the 2 nd cycle external assessment of the Programa de Melhoria do Acesso e da Qualidade da Atenção Básica conducted in 2014. The Statistical Package for Social Sciences was used to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 11 publications
0
14
0
11
Order By: Relevance
“…15 Although, in the analysis of the program to improve access and quality of basic care, the number of confirmed cases of TB and symptomatic respiratory diseases, reached 81.1% in the FHS throughout Brazil. 16 In theory, they all serve as a gateway to both the diagnosis of the disease and to alleviate more serious symptoms, as well as direct access to medical consultation and/or other services. 17 However, it is necessary to improve primary health care, as organizer of care and guarantee of access to avoid the delay of diagnosis and treatment that have repercussions in the control of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although, in the analysis of the program to improve access and quality of basic care, the number of confirmed cases of TB and symptomatic respiratory diseases, reached 81.1% in the FHS throughout Brazil. 16 In theory, they all serve as a gateway to both the diagnosis of the disease and to alleviate more serious symptoms, as well as direct access to medical consultation and/or other services. 17 However, it is necessary to improve primary health care, as organizer of care and guarantee of access to avoid the delay of diagnosis and treatment that have repercussions in the control of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Considered a priority by the Brazilian government since 2003, TB has been the subject of several national agreements and has been made a priority of the National Tuberculosis Control Program (NTCP). There has been an increase in the detection of cases through the strengthening of the primary health care services system [28].…”
Section: Discussionmentioning
confidence: 99%
“…Clementino et al 67 , when analyzing the health actions directed at people with tuberculosis in PC based on data from the second cycle of the PMAQ, found that 81.1% of the FHS teams in Brazil had an annual estimate of the number of confirmed cases of tuberculosis and respiratory symptoms. In contrast, only 48% of the teams had records of case follow-up and directly observed treatment.…”
Section: Advances and Problems In The Quality Of The Brazilian Phcmentioning
confidence: 99%